Caspase activation counteracts interferon signaling after G2 checkpoint abrogation by ATR inhibition in irradiated human cancer cells - Eek Mariampillai, Adrian; Hauge, Sissel; Øynebråten, Inger; Rødland, Gro Elise; Corthay, Alexandre; Syljuåsen, Randi G. (Frontiers in Oncology, 2022)
Recent studies suggest that inhibition of the ATR kinase can potentiate radiation-induced antitumor immune responses, but the underlying mechanisms and their impact in human cancers remain scarcely understood. We aimed to assess whether the ATR inhibitors VE822 and AZD6738, by abrogating the G2 checkpoint, increase cGAS-mediated type I IFN response after irradiation in human lung cancer and osteosarcoma cell lines. Supporting that the checkpoint may prevent IFN induction, radiation-induced IFN signaling declined when the G2 checkpoint arrest was prolonged at high radiation doses. G2 checkpoint abrogation after co-treatment with radiation and ATR inhibitors was accompanied by increased radiation-induced IFN signaling in three out of five cell lines tested, and apparently weakly in further one cell line. Consistent with cGAS-detected cytosolic DNA from ruptured micronuclei after G2 checkpoint abrogation, cGAS co-localized with micronuclei, and depletion of cGAS or STING abolished the IFN responses. Contrastingly, one lung cancer cell line showed no increase in IFN signaling despite irradiation and G2 checkpoint abrogation. This cell line showed a higher level of the exonuclease TREX1 than the other cell lines, but TREX1 depletion did not enhance IFN signaling. Rather, addition of a pan-caspase inhibitor restored the IFN response in this cell line. These results show that treatment-induced caspase activation can suppress the IFN response after co-treatment with radiation and ATR inhibitors. Caspase activation thus warrants further consideration as a possible predictive marker for lack of IFN signaling.